Determinants of Anemia on Pregnant Women in Sitinjak Health Center South Tapanuli District - Nur Arfah Nasution; Haslinah Ahmad; Anto J. Hadi (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Anemia in pregnant women is a health problem during pregnancy that is influenced by low iron consumption. Anemia in pregnancy is a maternal condition where the hemoglobin level is below 11 gr/dl. This research aims to analyze the determinants of the incidence of anemia in pregnant women at the Sitinjak Health Center, South Tapanuli Regency. This type of research is quantitative with a cross-sectional study approach. The population and sample were all pregnant women who visited and underwent antenatal care examinations at the Sitinjak Health Center, South Tapanuli Regency. A total of 68 pregnant women and sampling techniques were carried out for the total sample. The research instrument used a questionnaire and checked the Hb of pregnant women using a Hb meter. Data processing and analysis using chi-square and multiple logistic regression. The results of this study showed that maternal age (p= 0.027), parity (p= 0.027), nutritional status (p= 0.005), ANC frequency (p= 0.012), compliance with Fe tablet consumption (p= 0.002) were significantly related to the incidence of anemia. in pregnant women and the variable most related to the incidence of anemia is nutritional status with a value of Exp (B) = 3.411. The conclusion was obtained that the incidence of anemia in pregnant women is caused by factors such as age, parity, nutritional status, frequency of ANC, and compliance with the consumption of Fe tablets. So it is necessary to increase antenatal care visits in IEC health efforts (communication, information, education) related to anemia in pregnant women.